Preferred reporting items for journal and conference abstracts of systematic reviews and meta-analyses of diagnostic test accuracy studies (PRISMA-DTA for Abstracts): checklist, explanation, and elaboration. (15th March 2021) - Cohen, Jérémie F; Deeks, Jonathan J; Hooft, Lotty; Salameh, Jean-Paul; Korevaar, Daniël A; Gatsonis, Constantine; Hopewell, Sally; Hunt, Harriet A; Hyde, Chris J; Leeflang, Mariska M; Macaskill, Petra; McGrath, Trevor A; et al.
Abstract : For many users of the biomedical literature, abstracts may be the only source of information about a study. Hence, abstracts should allow readers to evaluate the objectives, key design features, and main results of the study. Several evaluations have shown deficiencies in the reporting of journal and conference abstracts across study designs and research fields, including systematic reviews of diagnostic test accuracy studies. Incomplete reporting compromises the value of research to key stakeholders. The authors of this article have developed a 12 item checklist of preferred reporting items for journal and conference abstracts of systematic reviews and meta-analyses of diagnostic test accuracy studies (PRISMA-DTA for Abstracts). This article presents the checklist, examples of complete reporting, and explanations for each item of PRISMA-DTA for Abstracts.